Ethoxysanguinarine, a Novel Direct Activator of AMP-Activated Protein Kinase, Induces Autophagy and Exhibits Therapeutic Potential in Breast Cancer Cells - Si, Yuan; Wang, Jiu; Liu, Xuewen; Zhou, Tong; Xiang, Yuchen; Zhang, Te; Wang, Xianhui; Feng, Tingting; Xu, Li; Yu, Qingqing; Zhao, Huzi; Liu, Ying (Frontiers in Pharmacology, 2020)
Ethoxysanguinarine (Eth) is a benzophenanthridine alkaloid extracted from Macleaya cordata (Willd) R. Br. It possesses antibacterial and antiviral activities and offers therapeutic benefits for the treatment of respiratory syndrome virus-induced cytopathic effects. However, the effect of Eth on human tumors and its pharmacological effects remain to be elucidated, together with its cellular target. Here, we examined the effects of Eth on breast cancer (BC) cells. We found that at low doses, Eth strongly inhibited the viability of BC cell lines and induced autophagy .Mechanistic studies showed that Eth induced autophagy by upregulating the activity of the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin complex 1 (mTORC1) signaling pathway. The AMPK inhibitor Compound C significantly attenuated Eth-induced autophagy and inhibited proliferation. Meanwhile, the AMPK activator metformin significantly enhanced Eth-induced autophagy and inhibited proliferation. Computational docking and affinity assays showed that Eth directly interacted with the allosteric drug and metabolite site of AMPK to stabilize its activation. AMPK was less activated in tumor samples compared to normal breast tissues and was inversely associated with the prognosis of the patients. Moreover, Eth exhibited potent anti-BC activity in nude mice and favorable pharmacokinetics in rats.